THE USE OF KAHOOT AS A LEARNING MEDIA FOR READING SKILLS - Romiza Ikbar (Lingustic, Literature and English Education, 2025)
This paper analyzes research studies examining the effectiveness of Kahoot as an instructional media application in improving student engagement, motivation, and learning outcomes. The review synthesizes findings from various studies that highlight the strengths and limitations of using Kahoot in educational settings. The results suggest that Kahoot fosters interactive and engaging learning environments, promotes active participation, and enhances knowledge retention. However, challenges such as technical issues and overreliance on gamified elements are noted. Future research directions are proposed to optimize the use of Kahoot in diverse educational contexts.